Image processing and analysis methods for the Adolescent Brain Cognitive Development Study - Hagler, Donald J.; Cornejo, M. Daniela; Makowski, Carolina; Dick, Anthony Steven; Sutherland, Matthew T.; Harms, Michael P.; Watts, Richard; Bjork, James M.; Garavan, Hugh P.; Hilmer, Laura; Pung, Christopher J.; Sicat, Chelsea S.; et al. (NeuroImage (Orlando, Fla.), 2019)
The Adolescent Brain Cognitive Development (ABCD) Study is an ongoing, nationwide study of the effects of environmental influences on behavioral and brain development in adolescents. The main objective of the study is to recruit and assess over eleven thousand 9-10-year-olds and follow them over the course of 10 years to characterize normative brain and cognitive development, the many factors that influence brain development, and the effects of those factors on mental health and other outcomes. The study employs state-of-the-art multimodal brain imaging, cognitive and clinical assessments, bioassays, and careful assessment of substance use, environment, psychopathological symptoms, and social functioning. The data is a resource of unprecedented scale and depth for studying typical and atypical development. The aim of this manuscript is to describe the baseline neuroimaging processing and subject-level analysis methods used by ABCD. Processing and analyses include modality-specific corrections for distortions and motion, brain segmentation and cortical surface reconstruction derived from structural magnetic resonance imaging (sMRI), analysis of brain microstructure using diffusion MRI (dMRI), task-related analysis of functional MRI (fMRI), and functional connectivity analysis of resting-state fMRI. This manuscript serves as a methodological reference for users of publicly shared neuroimaging data from the ABCD Study. •An overview of the MRI processing pipeline for the ABCD Study.•A discussion on the challenges of large, multisite population studies.•A methodological reference for users of publicly shared data from the ABCD Study.•Preliminary results from technical survey of baseline dataset.